1975
DOI: 10.1139/v75-427
|View full text |Cite
|
Sign up to set email alerts
|

Photoreaction of Nitroso Compounds in Solution. Part XXXI. Mechanisms of Intramolecular Acid Catalyzed Cleavage Reactions and a Hydride Initiated Rearrangement of C-Nitroso Alkanes

Abstract: CHOW. Can. J. Chem. 53,3014(1975).Two novel rearrangements of nitroso alkanes, one intramolecular acid catalyzed cleavage reaction and the other ring enlargement during hydride reduction, are described. Aminium radical initiated addition to norbornene under nitrogen gave cis-exo-and trans-2-nitroso-3ammonium norbornanes in a good yield. Whereas the trans isomer underwent the usual nitroso group reactions, i.e., tautomerization, dimerization, and HNO addition, the cis-exo isomer and its hydroxy analog cleaved e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…In a recent direct example, nitroxyl derived from Angeli's salt (Na 2 N 2 O 3 , an O-diazeniumdiolate, see later) was trapped by nitrosobenzene to produce Cupferron. 82 The reaction also explains the production of diazeniumdiolates in the photolysis of N-nitrosoamines in the presence of olefins [83][84][85] (via addition of HNO formed from the N-nitrosoamine to the C-nitroso compound formed by addition of the N-nitrosoamine to the olefin) and in the reaction of monoalkylhydroxylamines with nitric oxide. 86 Conversion of C-nitroso dimers to diazeniumdiolates was first reported in 1895.…”
Section: Transformations Of C-nitroso Compoundsmentioning
confidence: 98%
“…In a recent direct example, nitroxyl derived from Angeli's salt (Na 2 N 2 O 3 , an O-diazeniumdiolate, see later) was trapped by nitrosobenzene to produce Cupferron. 82 The reaction also explains the production of diazeniumdiolates in the photolysis of N-nitrosoamines in the presence of olefins [83][84][85] (via addition of HNO formed from the N-nitrosoamine to the C-nitroso compound formed by addition of the N-nitrosoamine to the olefin) and in the reaction of monoalkylhydroxylamines with nitric oxide. 86 Conversion of C-nitroso dimers to diazeniumdiolates was first reported in 1895.…”
Section: Transformations Of C-nitroso Compoundsmentioning
confidence: 98%
“…146 Similarly, dimethylnitrosamine undergoes photoaddition to norbornene (eq 18). 147 An interesting analogous synthesis is provided by the photoaddition of N-nitrosopiperidine to phenylacetylene followed by hydrolysis to form phenylglyoxal ketoxime, which tautomerizes to give the dimer of 1-nitroso-2-hydroxystyrene (Scheme 10), 148 a compound which merits a full structural study.…”
Section: Addition Of N-nitroso Compoundsmentioning
confidence: 99%
“…The next lower signal centered at T 6.57, equivalent in intensity to four protons, could be assigned to the C-2 and C-6 protons. The unusually low ?-values for protons geminal to an amine group had been observed in another hydroxylamine derivative (54), and suggested that 22 might be a zwitterion in which the amine group was protonated by the nearby weakly acidic Nnitrosohydroxylamino group.…”
Section: Nhcho H 24 25mentioning
confidence: 86%